Generalized Yang Poisson Models on Canonical Phase Space - Martinić Bilać, Tea; Meljanac, Stjepan; Mignemi, Salvatore (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
We discuss the generalized Yang Poisson models. We construct generalizations of the Yang Poisson algebra related to (1, 5) Algebra discussed by Meljanac and Mignemi (2023). The exact realizations of this generalized algebra on canonical phase space are presented, and the corresponding differential equations are solved in simple cases. Furthermore, we discuss the Poisson algebras related to (3, 3) and (2, 4) algebras.